Sleep Quality and Stress Symptoms in Mexican University Women During the COVID-19 Pandemic - Garcia Estrada, Linda Isis; Yánez Peñuñuri, Libia Yanelli (Uptc, 2023)
The objective of the research was to analyze the relationship between sleep quality and stress symptoms in Mexican university women during the COVID-19 pandemic. The study was cross-sectional and correlational in nature. One hundred Mexican university women between 18 and 27 years of age participated. Once the informed consent was signed, the Pittsburgh Sleep Quality Index instrument and an ex profeso questionnaire to evaluate stress were applied. Descriptive statistical analyses and chi-square tests were performed. A close relationship was found between sleep quality—with the components of sleep duration and sleep latency—and stress and symptoms of stress in women during the COVID-19 pandemic, which in turn influenced the development of the person’s well-being, manifesting physiological, psychological and social changes. Intervention programs for the promotion of sleep hygiene are recommended.